(untitled) (Journal of Soft Computing Exploration, 2024)
The communication process for notifications involves sending alerts to users through a combination of automation and telecommunications technologies. The design smart trash, utilizing the Wemos microcontroller, performs various automated tasks such as opening and closing, compacting the garbage, and providing status notifications. These notifications are transmitted through the Firebase web server communication and an Android application on smartphones. Following successful testing, the system functions according to the programmed specifications. It achieves automatic opening and closing within a proximity range of ≤ 10 cm, demonstrates an average waste compaction rate of 45%, and delivers notifications to users indicating the trash status—whether it’s empty, halfway full, or completely full.